Determination of soil density by cone index data. (June 2018) - Pillinger, György; Géczy, Attila; Hudoba, Zoltán; Kiss, Péter
Highlights: Soil density and CI experiments in soil tank. The relationship between soil density and relative elongation. Calculation of relative vertical deformation. Nomogram to determine the relative elongation from soil density. Soil density calculation from the cone index data. Abstract: In this paper a novel soil-density determination method is presented. The classic method (sampling, drying, mass measuring, etc.) can give proper results for the given problem but the standard methodology requires a lot of practical effort. While the soil is generally inhomogeneous, the measured density values of the soil sample applies only for the sample itself. On the entire soil territory this density can be interpreted only with significant errors. For a better mapping of the soil-density distribution expansive measurements are required. The task is complicated by the determination of density distribution in deeper layers of the soil as well. Our work presents a simpler method to determine the soil-density distribution in deeper layers with the use of cone penetration test (CI) results. With this method we can obtain detailed results of the soil-density distribution in deeper layers that may help further calculations for soil deformation analysis such as an exact determination of the soil sinkage below a tire track.